EVALUASI DAMPAK PERA NOMOR 7 TAHUN 2010 KOTA TENTANG PENATAAN RUANG TERBUKA HIJAU KOTA SEMARANG (Studi di Kecamatan Candisari Kota Semarang) - Esra Oktavia Siahaan; Slamet Santoso; Dyah Lituhayu (Journal of Public Policy and Management Review, 2018)
The role of green public space in our urban environment isas an important provider of ecological functions such as preventing flood, reducing air pollution, and reducing the temperature of the air. The Government of Semarang city publish the local regulation of Semarang number 7 in 2010 about a regulation of arrengement of green space as one effort to resolve arrengement green open sapce in Semarang. There is still a lack of green open space in Kecamatan Candisari which is the background of this research. The research is aimed to evaluate impact the local regulation of Semarang number 7 in 2010 about a regulation of arrengement of green space in district Candisari, Semarang. The implementer in this policy is the Bappeda, Department of Spatial Planning, Department of Housing and Settlements, and Department of Enviroment of Semarang City. The research uses the principal of policy implementation according to Riant Nugroho like, right policy, proper executor, right target, right environment, and proper process and impact evaluation according to Samudra Wibawa of authority like, individual impact, organization and group impact, society impact and social impact culture. The research method is qualitative and the data collection techniques are interviews, observation, and documentation. The results of the local regulation of Semarang number 7 in 2010 about a regulation of arrengement of green space in Candisari district is not maximum with the goals. This is due to the lack of green open space and lack of public participation in increasing green open space on social life in Candisari District.